Squamous cell carcinoma–related oncogene (SCCRO) neddylates Cul3 protein to selectively promote midbody localization and activity of Cul3(KLHL21) protein complex during abscission - Huang, Guochang (J Biol Chem, 2017)
Squamous cell carcinoma–related oncogene (SCCRO)/DCUN1D1, a component of the neddylation E3 complex, regulates the activity of the cullin–RING–ligase type of ubiquitination E3s by promoting neddylation of cullin family members. Studies have shown that SCCRO regulates proliferation in vitro and in vivo. Here we show that inactivation of SCCRO results in prolonged mitotic time because of delayed and/or failed abscission. The effects of SCCRO on abscission involve its role in neddylation and localization of Cul3 to the midbody. The Cul3 adaptor KLHL21 mediates the effects of SCCRO on abscission, as it fails to localize to the midbody in SCCRO-deficient cells during abscission, and its inactivation resulted in phenotypic changes identical to SCCRO inactivation. Ubiquitination-promoted turnover of Aurora B at the midbody was deficient in SCCRO- and KLHL21-deficient cells, suggesting that it is the target of Cul3(KLHL21) at the midbody. Correction of abscission delays in SCCRO-deficient cells with addition of an Aurora B inhibitor at the midbody stage suggests that Aurora B is the target of SCCRO-promoted Cul3(KLHL21) activity. The activity of other Cul3-anchored complexes, including Cul3(KLHL9/KLHL13), was intact in SCCRO-deficient cells, suggesting that SCCRO selectively, rather than collectively, neddylates cullins in vivo. Combined, these findings support a model in which the SCCRO, substrate, and substrate adaptors cooperatively provide tight control of neddylation and cullin–RING–ligase activity in vivo.